Pengenalan dan Pelatihan Menulis Teks Bahasa Inggris: Get More Insight and Improve Your English Skill (Academic Writing Skill) di SMAN 1 - Andi Mega Januarti Putri; Putu Wahyu Sudewi; Nurul Imansari (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This Community Service aims at helping students of the SMA 1 Karrosa to write an academic text in English. The presentation material consists of the concepts of writing comprehension to write description paragraphs in English in various themes in writing descriptions of people, objects, and places. The methods used are lecturing, discussion, assignment, training, evaluation, and feedback. The result of this training is that students of SMA 1 Karrosa have high enthusiasm and motivation in learning English particularly in writing paragraph in English. Moreover, this training can improve students' ability to write a paragraph in English, individually, in pairs, or in group. It also increases the competence of students in the field of writing text or other forms of academic writing and has a very positive impact on students in completing daily school or assignments and also as capital in preparing other assignments.It can be seen on the attendance of students during the three months training which was 86%, four out of seven groups of student are alsoto able to write academic text in English, and questionnaire results showed that 87% of students give positive response which 87% of them claimed to know Engish Academic Writing thorugh this training and 75% of the students answered they can now write English Academic Text through this training and activity.